The Spiderwick chronicles [videorecording] - Paramount Pictures Corporation; Nickelodeon Movies; Kennedy/Marshall Company; Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment)
The moment the Grace family moves into the dilapidated Spiderwick Estate, strange things begin to happen. Jared is a curious, adventurous boy who quickly seeks out and finds the hidden laboratory of his great great uncle Arthur Spiderwick. He unleashes a mysterious force when he locates a field guide full of the secrets of the magical creatures that inhabit the forest surrounding the mansion. His twin brother Simon is calm and reserved. He is the intellectual twin, but is rapidly drawn into the fantastical world of fairies and goblins. Older sister Mallory and their mom are harder to convince, but after the almighty and ruthless ogre leader Mulgarath begins to attack the home, the entire family must band together to combat the hordes of goblins and creatures that lurk just outside.